PENGEMBANGAN E-BOOK FISIKA BERBASIS SOCIO SCIENTIFIC ISSUE (SSI) BERBANTUAN HEYZINE FLIPBOOK PADA MATERI FLUIDA STATIS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN KOLABORASI PESERTA DIDIK - Hidayat Tullah; Ananda Aprilia; Wipsar Sunu Brams Dwandaru (Jurnal Penelitian Pendidikan IPA, 2025)
Integrating Socio Scientific Issues (SSI) in physics learning encourage students to actively discuss a problem, understand the nature of science, consider the controversies and their influence on the world both physically and socially. This research aims to produce an e-book on Static Fluid topic based on SSI assisted by Heyzine Flipbook, which is suitable for use to improve students' critical thinking and collaboration skills and determining its effectiveness. This method used in this study is research and development (R&D) with the define, design, develop, and disseminate (4D) model. The define stage aims to determine what is needed in the e-book development. The design stage is designing the e-book based on a certain format. The develop stage involves making the products, namely the e-book and instruments. The disseminate stage involves widespread distribution of the e-book that has been developed. The research result shows that the e-book based on SSI assisted by Heyzine Flipbook is valid based on the evaluation of physics experts and teachers, as well stated valid with very good category by the students’ responses. The e-book helps students to increase their abilities to think critically and collaborate in the classroom.